Role of Helicobacter Pylori Infection and Nonsteroidal Anti-Inflammatory Drug Use in Bleeding Peptic Ulcers: Anti-Inflammatory Drug Use in Bleeding Peptic Ulcers - Irshad, Zainab; Sajjad Khan, Muhammad; Kamran, .; Sohail, Muhammad; Fahim, Muhammad; Naeem, Sundus; Ur Rashid, Salman; Rubina Gillani, Syeda (Pakistan Journal of Health Sciences, 2023)
Most peptic ulcers and their complications are caused by Helicobacter pylori and nonsteroidal anti-inflammatory drugs (NSAIDs). Objective: To characterize the bleeding peptic ulcers features. Methods: This prospective study was carried out on 124 cases in the Department of Gastroenterology, Lady Reading Hospital in collaboration with Pharmacology Unit of Khyber Medical University, Peshawar from July 2018 to June 2020. All the patients were categorized into four groups: Positive H. pylori and no NSAID history (Group I), Positive H. pylori and NSAID use (Group-II), Negative H. pylori and NSAID user (Group-III), and Negative H. pylori and no NSAID history (Group-IV). Data analysis was carried out in SPSS version 26. Results: Of the total 124 cases, the prevalence of positive and negative H. pylori infection was 77.4% (n=96) and 22.6% (n=28) respectively. The number of patients in group I, II, III, and IV patients were 80 (64.5%), 16 (12.9%), 17 (13.7%), and 11 (8.9%) respectively. The incidence of NSAID users were 33 (26.6%) patients, out of which 18 used on daily basis and 15 on demand. Those in groups I and IV were substantially younger than groups II and III and they had less comorbid disorders than patients in group I. Conclusion: The present study concluded that about 26.6% of patients with bleeding ulcers took NSAIDs, meaning that low-dose aspirin will cause bleeding ulcers as will NSAID use on-demand.